Netnography of The Linkages Between Celebrity Worship and Impulsive Buying on a Treasure Album Product - Rizky Mawadatul Rahmah; Rini Anggriani; Lady Faerrosa (Postgraduate, University of Mataram, 2023)
The Korean Wave has become a prevailing trend around the world in recent years. Many people has begun to recognize South Korean culture through movies, drama series, and music. South Korea has its own music genre called Korean Pop as known as K-Pop. One of the most popular K-Pop groups in Indonesia is Treasure. The purpose of this research is to discover and explore the linkages between celebrity worship and impulsive buying of Treasure album products by fans. Using a descriptive qualitative method with a netnographic approach. Therefore, this study observed the behavior, discussion, and interaction of Treasure fans on Twitter. Especially on @ygent_official and @treasuremenfess accounts. The results of this study found that celebrity worship and impulsive buying are closely related, as enthusiastic fans welcome their idol groups who release new albums after a long hiatus. Fans who did impulsive buying are mostly fans who pre-order spontaneously without planning.